IMPLEMENTATION OF THE FAMILY PLANNING VILLAGE PROGRAM IN UJUNGE VILLAGE, MADELLO VILLAGE, BALUSU DISTRICT, BARRU DISTRICT - Ismail, Andi Muhammad Ishak; Marsuki; A.Ariyadi (P3M Stia Al Gazali Barru and Meraja media, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal